Elliptic Integrals, Elliptic Functions and Modular Forms in Quantum Field Theory - Blümlein, Johannes; Schneider, Carsten; Paule, Peter (Texts & Monographs in Symbolic Computation, 2019)
This book includes review articles in the field of elliptic integrals, elliptic functions and modular forms intending to foster the discussion between theoretical physicists working on higher loop calculations and mathematicians working in the field of modular forms and functions and analytic solutions of higher order differential and difference.